4(2x-1)=2(3x-2)

Simple and best practice solution for 4(2x-1)=2(3x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-1)=2(3x-2) equation:


Simplifying
4(2x + -1) = 2(3x + -2)

Reorder the terms:
4(-1 + 2x) = 2(3x + -2)
(-1 * 4 + 2x * 4) = 2(3x + -2)
(-4 + 8x) = 2(3x + -2)

Reorder the terms:
-4 + 8x = 2(-2 + 3x)
-4 + 8x = (-2 * 2 + 3x * 2)
-4 + 8x = (-4 + 6x)

Add '4' to each side of the equation.
-4 + 4 + 8x = -4 + 4 + 6x

Combine like terms: -4 + 4 = 0
0 + 8x = -4 + 4 + 6x
8x = -4 + 4 + 6x

Combine like terms: -4 + 4 = 0
8x = 0 + 6x
8x = 6x

Solving
8x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
8x + -6x = 6x + -6x

Combine like terms: 8x + -6x = 2x
2x = 6x + -6x

Combine like terms: 6x + -6x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| (3a/4)+5=(5a/6)+2 | | 3a/4+5=5a/6+2 | | (3x+18)93=180 | | (x+1)(x+11)=-14 | | 9+4lnx=14 | | w-4=3 | | (x^2-9)/(x+4)(x+3)=0 | | (2n+6)/3=((9n-4)/5)-n | | -2+15=17x-4-16x | | 5a=4a-7 | | 10=0.3521x^5-7.5096x^4+72.227x^3-329.33x^2+674.35x-412.13 | | X^3-x^2-2x+5=0 | | 7x+18=67 | | 0.1x^2-0.2x-0.1=0 | | (x+4)(x+4)=88 | | x-(2x+1)-8+3=3-(3x+3) | | 10x+16=86 | | 3x+16=37 | | (10n)7= | | 8-(2x+1)-8+3=3-(3x+3) | | 98-9x=4x+7 | | 3.1+(8.6+m)= | | P=5h+5u | | ((x^2-9)/(x^2+7x+12))/((x^2-4x-32)/(x^2-3x)) | | -4n+18=-2n-18 | | 8x+b+4x= | | 1-3.5t=1.4-2.33t+1.5 | | 3f+4k-5f= | | -5=5t+5 | | 8x^4+35x^2+12=0 | | P=10 | | 0=-5p(-3q)+(4m)(-6n) |

Equations solver categories